Fiscal Expectations Under the Stability and Growth Pact : Evidence from Survey Data - Poplawski Ribeiro, Marcos; Rulke, Jan-Christoph. (Washington, D.C. : International Monetary Fund, 2011)
The paper uses survey data to analyze whether financial market expectations on government budget deficits changed in France, Germany, Italy, and the United Kingdom during the period of the Stability and Growth Pact (SGP). Our findings indicate that accuracy of financial expert deficit forecasts increased in France. Convergence between the European Commission's and market experts' deficit forecasts also increased in France, Italy, and the United Kingdom, particularly during the period after SGP's reform in 2005. Yet, convergence between markets' forecasts and those of the French, German, and Italian national fiscal authorities seems not to have increased significantly during the SGP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet